The selection process of sponsors and sponsees and the process of developing the sponsorship deal - Σαρλή, Έλενα (Πανεπιστήμιο Πελοποννήσου, 2010)
Due to the increasing financial value of sport sponsorship, the selection of a sponsorship partner and the development of the sponsorship deal are crucial issues for sport sponsorship partners. This is a qualitative study which examines the sponsorship selection and development process among 3 “sponsorship triads”. The researcher conducted nine thorough focused interviews with all of the sport properties and their sport sponsors examined in order to gain a deeper understanding on how sport sponsors and sport properties decide upon sponsorship proposals and on the stages through which the sponsorship process develops. The findings are analysed and the results showed that the selection criteria vary according to each corporation’s special needs and characteristics. Revenue opportunities, image enhancement gained through the sponsorship, the match of target markets and the prospective contract’s terms are important selection criteria in the selection process. Duration of the agreement, quality of relationship and special criteria according to each prospective partner’s industry are moderating factors. Sponsors and sponsees have a structured process in place which is very alike new service development and the sponsorship development process is comprised by 3 phases. The information collection phase, the proposal preparation and presentation or receipt phase and the negotiations and contract sign phase. Managerial implications are also presented followed by a section which addresses the limitations of the study and suggests recommendations for future research.
Keywords: Χορηγία, Αθλητική; Football sponsorship; Sponsorship decision-making; Sponsorship acquisition